THE RELATIONSHIP OF TIME PERCEPTION AND IMPULSIVENESS OF UKRAINIAN STUDENTS - Луценко, Олена Львівна; Сеник, Оксана Мирославівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
Identifying the relationship between characteristics of the individual perception of time and the personality trait of impulsivity is the problem this study is devoted to. The aim of the study is to analyze the relationships between the various components of impulsiveness as a personality trait and the characteristics of an individual minute (IM) taking into account age and gender in a sample of Ukrainian university students (62 participants aged 17-22; 11 of them are men). To assess the features of time perception, the IM method was used according to F. Halberg. As the characteristics of MI, we used the mean and standard deviation for three consecutive measurements of IM and the average error of subjective time relative to objective one in percent. Impulsivity was measured using the UPPS-P Impulsive Behavior Scale test in the Ukrainian adaptation, which reveals 5 indicators of impulsivity: negative urgency, positive urgency, lack of premeditation, lack of perseverance, and sensation seeking. For Ukrainian students, impulsivity indicators correspond to the average norms of the French sample. The mean IM is 61.3 seconds and it is in the range of 36-88 seconds, the standard deviation of 3 IM measurements is 8 seconds, the average error of the subjective time relatively to the objective one was 9%. An inverse relationship between the mean duration of IM and the impulsivity index “positive urgency” was revealed. A direct relationship between the variability of the IM, the average error of the IM in percent and the impulsivity index “lack of perseverance” was also revealed. There are no signifiant differences in the mean duration of IM between men and women. At the same time, women have a signifiantly higher variability in time estimation – the standard deviation of IM is signifiantly greater in them than in men. By the characteristics of the impulsiveness, women have a signifiantly higher indicator of positive urgency than men. Age-related differences in the features of perception of time and impulsivity were not found. It will be worth to study relations of IM with other personality peculiarities such as Big Five traits and temperament types. This would give us more insights about diagnostical usefulness of IM measurements as proxy between physiological and psychological conditions of people.